Management of Faith and Qur'an Curriculum Development at Kuttab Al-Fatih Yogyakarta in Developing the Qur'anic Character of Students - M. Irfan Radin; Azam Syukur Rahmatullah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study analyzes the management of the Faith and Qur’an Curriculum development at Kuttab Al-Fatih Yogyakarta in shaping students’ Qur’anic character. The focus is on planning, organizing, implementing, and evaluating the curriculum based on Qur’anic and Hadith values. The research employed a qualitative descriptive method. Data were collected through interviews with the head of Kuttab, curriculum coordinators, and teachers, along with direct observation and documentation of learning activities. The findings show that curriculum planning is centralized, systematic, and comprehensive, emphasizing foundations, objectives, content, strategies, and learning resources. Organization involves leaders, coordinators, teachers, and management, guided by classical Islamic values. The implementation is successfully translated into classroom practices that nurture academic competence, faith, morals, and a Qur’anic worldview in students’ daily lives. Evaluation is conducted regularly, involving multiple stakeholders, ensuring continuous and systematic supervision. Overall, curriculum development management at Kuttab Al-Fatih has proven effective in fostering students’ Qur’anic character through integrating faith and Qur’anic values. However, flexibility and innovation are still required to address the challenges of modern education.